Starting out with amateur astronomy: equipment and software - Loke, Seng Cheong (Amazon Digital Services, 2014)
Getting started on a new hobby can be a daunting challenge when there are so many possibilities to consider. This is especially important for astronomy where equipment purchases can be quite expensive and a wrong decision leads to much regret and wasted time. This book aims to guide the budding amateur astronomer in making an informed choice in equipment and software purchasing.